A Theoretical Study of Deflection of AFM Bimaterial Cantilevers Versus Irradiated Position - Dat, Le Tri; Huy, Ho Thanh; Vy, Nguyen Duy (Communications in Physics, 2018)
The bimaterial cantilevers of atomic force microscopes have been widely used in chemical and bio-sensing. Due to the difference in the thermal expansion coefficients of the two layers, the cantilever is deflected and its deflections is dependent on the heat absorption from the ambient environment or the objects adsorbed on the cantilever surface. In this study, we theoretically examine the deflection of this cantilever considering different irradiated configurations of a laser beam and thicknesses of the coating layer. We show that the temperature difference between the end and the clamped position is maximized for an irradiation at the cantilever end and this difference reduces with increasing coating thickness. Especially, the maximal deflection is seen for an irradiation in the middle of the cantilever, around 0.6 of the cantilever length from the clamped position. The obtained results could help determining an irradiated configuration of laser and the coating thickness to optimize the sensitivity of the cantilevers in thermally sensing devices.